Discovery of intestinal microorganisms that affect the improvement of muscle strength - Ji-Seon Ahn; Hae-Mi Kim; Eui-Jeong Han; Seong-Tshool Hong; Hea-Jong Chung (Scientific Reports)
Abstract This study provides the first evidence related to the identification of microbial strains closely associated with muscle strength enhancement, independent of the host’s genetic background. Fecal transplants from humans into mice revealed a significant impact of gut bacteria on muscle strength, with some mice experiencing increases, while others showed no change or decreases. Interestingly, analysis of the fecal and gastrointestinal tract bacteria from each mouse classified by the degree of muscle strength revealed significant differences based on muscle strength. Furthermore, a more diverse microbial community was observed in the gastrointestinal tract compared to the feces. Further investigation identified two bacterial species, Lactobacillus johnsonii (L. johnsonii) and Limosilactobacillus reuteri (L. reuteri), that are related to improved muscle strength. Indeed, we confirmed that the supplementation with these bacteria in aged mice significantly enhanced their muscle strength by increasing the mRNA expression levels of follistatin (FST) and insulin-like growth factor-1 (IGF1) in muscle tissue. Overall, this study provides the first evidence that specific gut bacteria can directly improve muscle strength and introduces a novel approach to studying the gut microbiome’s influence on complex traits.